Safety Assessment of Bacillus subtilis G8 Isolated from Natto for Food Application - Putri, Nathania Calista; Victor, Hans; Litanto, Vivian; Pinontoan, Reinhard; Jo, Juandy (Universitas Gadjah Mada, 2024)
Various bacteria are widely used as food-fermenting agents, including Lactobacillus, Bifidobacterium, and Bacillus. Despite they are generally recognized as safe to be consumed by humans, those bacteria could potentially cause antibiotic resistance as they could acquire and transfer antibiotic resistance genes from or to other microbes within the human gastrointestinal tract. Profiling antibiotic resistance pattern in those bacteria is therefore important to control the spread of antibiotic resistance. In this study, antibiotic resistance profile of Bacillus subtilis G8 was assessed. B. subtilis G8 had been isolated from commercialised Japanese natto in Indonesia and had been previously reported for its fibrinolytic characteristics. The antibiotic resistance phenotype and genotype of B. subtilis G8 were assessed through the Kirby-Bauer disk diffusion method and whole-genome analysis, respectively. B. subtilis G8 exhibited resistance towards Oxacillin, Lincomycin and Tiamulin-Lefamulin. The bioinformatics analysis indicated several responsible genes mediating those resistance, i.e., ybxI (for Oxacillin), lmrB (for Lincomycin) and vmlR (for Lincomycin and Tiamulin-Lefamulin). All identified genes were found in the chromosomal DNA. Further analysis found no mobile genetic elements within the genome, therefore reducing a risk of resistance gene transfer via plasmid and subsequently supporting safety profile of B. subtilis G8 in food fermentation usage.